A Preliminary Investigation of Pentachlorobenzene Amount Created from Municipal Waste Incinerators and Industrial Furnaces at Some Provinces in Northern Vietnam - Hue, N.T.; Nam, H.; Tung, N.H. (Asian Journal of Chemistry, 2015)
Pentachlorobenzene is primarily formed from incomplete combustion processes. In this study, pentachlorobenzene amounts in residue ash and cinder from some municipal waste incinerators and industrial furnaces at four provinces in Northern Vietnam, including Hai Duong, Hanoi, Bac Ninh and Thai Nguyen, were preliminary investigated. The pentachlorobenzene amounts from the burners ranged from 0.0013 to 0.0325 mg kg-1 and from 0.0016 to 0.0390 mg kg-1 for the residue ash and cinder, respectively. The total pentachlorobenzene amounts of the residue ash and cinder in each provinces in 2014 ranged from 0.0070 to 0.0323 mg kg-1 and from 0.0016 to 0.0240 mg kg-1, respectively. Specifically, the total amounts of pentachlorobenzene of Hai Duong province, in the period from 2012 to 2014 ranged from 0.0070 to 0.0470 mg kg-1 and from 0.0046 to 0.0390 mg kg-1 for the residue ash and the cinder, respectively.